AKTIVITAS ANTIOKSIDAN DAN PROFIL FITOKIMIA EKTRAK ETANOL BAWANG DAYAK (Eleutherine bulbosa (Mill.) Urb - wati, Sri Rahmawati; Bachri, Moch. Saiful Bachri; Mulyaningsih, Sri Mulyaningsih; Widyaningsih, Wahyu Widyaningsih; Kaffah, Silmi Kaffah; Aisyah, Shafala Rivani Aisyah; Muhammad Ma’ruf (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
Excessive free radicals (Reactive Oxygen Species/ROS) can trigger oxidative stress, which contributes to various degenerative diseases. Antioxidants from natural ingredients, such as Dayak onion (Eleutherine bulbosa (Mill.) Urb.), are known to contain flavonoid and phenolic secondary metabolites that have the potential to ward off free radicals. Dayak onion bulbs were extracted with 96% ethanol, then analyzed for flavonoid and phenolic content using phytochemical analysis and confirmed with TLC using quercetin and gallic acid. Antioxidant activity was tested using the DPPH method. Ethanol extract of Dayak onion contains flavonoids and phenolics based on TLC results showing a flavonoid Rf value of 0.93 (close to quercetin 0.86) and phenolic Rf value of 0.93 (different from gallic acid 0.37). Antioxidant activity testing yielded an IC₅₀ value of 106.18 ppm (moderate category), while quercetin had an IC₅₀ of 9.94 ppm (very strong category). Ethanol extract of Dayak onion was found to contain flavonoids and phenolics detected through phytochemical and TLC tests, and had moderate antioxidant activity based on the DPPH test. These findings support the potential of Dayak onion as a natural source of antioxidants for the prevention of oxidative stress.